A dog wearing shoes - Ko, Sangmi (New York : Schwartz & Wade Books, 2015)
Mini finds a dog in the park wearing shoes but no collar and begs to keep him, but soon she realizes that whoever put the shoes on him loves the dog, as well.
School Library Journal, June 2015
Kirkus Starred, July 2015
Booklist, September 2015
2.0
K-3
Keywords: Dogs -- Juvenile fiction; Lost articles -- Juvenile fiction; Dogs -- Fiction; Lost and found possessions -- Fiction; Dogs -- Fiction; Lost and found possessions -- Fiction